VALIDATING THE HADITH ON EATING HABITS OF BELIEVERS AND DISBELIEVERS: A STUDY OF THE TAḤLĪLĪ HADITH IN SUNAN IBN MAJAH (NO. 3256) - Firdaus, Gita Roihanatul; Lestari, Jannatul Nur Fitriani (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
Understanding certain hadith requires more than just a textual understanding; it also requires a contextual understanding. This research discusses the analysis of the degree of a hadith and its understanding found in Sunan Ibn Majah, number 2356. If this hadith text is used as a reference to judge someone's faith, it is possible that a believer may be considered a disbeliever simply because they eat a large portion of food. There are several literature discussing this hadith, but they have not been able to provide complete data, whether in terms of the chain of narrators (sanad) or the content (matan) of the hadith. This research uses an inductive qualitative method, which involves obtaining data and information by collecting classical Islamic texts that explain the degree of hadith and books on understanding hadith, among others, to strengthen arguments and determine the position of the hadith in order to preserve its accuracy. The degree of this hadith is considered authentic (sahih), and the understanding of the hadith is that it refers to the difference in the amount of food consumed by a believer and a disbeliever. [Dalam memahami sebagian hadis tidak cukup dengan memahaminya secara tekstual saja, melainkan juga harus secara kontekstual. Penelitian ini membahas tentang analisis derajat hadis dan pemahamannya yang terdapat di kitab Sunan Ibnu Majah nomor 2356. Jika teks hadis ini dijadikan acuan untuk menilai keimanan seseorang maka bisa jadi orang yang beriman dianggap menjadi kafir hanya karena porsi makan yang banyak. Ada beberapa literatur yang membahas tentang hadis tersebut, akan tetapi masih belum bisa menyajikan data yang lengkap, entah dari segi sanad maupun matan hadis tersebut. Penelitian ini menggunakan metode induktif kualitatif yaitu memperoleh data dan informasi dengan mengumpulkan kitab turaṡ, yang menjelaskan tentang derajat hadis maupun kitab pemahaman hadis dan lain-lain, guna memperkuat argumen agar mengetahui kedudukan hadis tersebut sehingga dapat menjaga keakuratan hadis. Derajat hadis tersebut bernilai sahih dan pemahaman hadis tersebut adalah perbedaan makan orang mukmin yang sedikit, dan orang kafir yang banyak.]